The climate of the past millennium and online public engagement in a scientific debate. (26th May 2019) - Zorita, Eduardo
Abstract: After the publication in 1999 of a reconstruction of the Northern Hemisphere temperature popularly known as "the hockey‐stick, " climate scientists and Internet bloggers engaged in a heated and often stalemated public debate on the validity of paleoclimate reconstructions and on their implications for the wider question of anthropogenic climate change. The Internet emerged as an important medium for channeling the direct participation of the public almost at the same level as the professional climate scientist. It also allowed dissemination of largely unfiltered information. I argue that, although paleoclimate research did benefit in some technical aspects, the public debate around the hockey‐stick focused on issues that were not scientifically central, like the existence of the Medieval Warm Period or the characterization of 1998 as the warmest year of the millennium. In contrast, much more relevant points, such as constraining the value of climate sensitivity using reconstructions of past climate, remained restricted within purely academic circles. The public resonance of the hockey‐stick debate was also clearly framed by the politicization of climate science and the impacts of the series of IPCC reports, in particular the Third Assessment Report, published in 2001. This resonance was amplified by the expanding use of the Internet. The Internet represented a new bidirectional channel through which the public and academia could interact to achieve a transparent, democratic, and participative evaluation of science. I argue that, although we could have hoped for a positive outcome of the hockey‐stick controversy, this opportunity for a new constructive public engagement in scientific debates was missed. This article is categorized under: Paleoclimates and Current Trends > Paleoclimate Social Status of Climate Change Knowledge > Sociology/Anthropology of Climate Knowledge Abstract : Diverging attention in the blogosphere on two concepts sorrounding the hockey‐stick debate: the attention on 'Medieval Warm Period' spiked in the period around Climate‐Gate (December 2009); in contrast, the internet attention on the much more important concept of 'climate sensitivity' was not affected, and has continuously decreased over the past 15 years. The plot is the result o fa Google‐Trend search of both terms.